Culturally Responsive Strategies Used to Deliver Ethnic-Specific Services to Asian Americans. Issue 4 (October 2014) - Weng, Suzie S.; Netting, F. Ellen
Studies focused on a continuum of service delivery forms that target Asian Americans are examined: (a) ethnic agencies serving Asian and other ethnic groups, (b) pan-Asian ethnic agencies, and (c) ethnic agencies targeting specific Asian groups. Culturally responsive strategies being used to develop these Asian-specific service programs are identified, as well as assumptions/themes that undergird organizational identity, frame organizational culture, and guide practice.